Electroacupuncture Confers Antinociceptive Effects via Inhibition of Glutamate Transporter Downregulation in Complete Freund's Adjuvant-Injected Rats. (23rd August 2012) - Kim, Ha-Neui; Kim, Yu-Ri; Jang, Ji-Yeon; Shin, Hwa-Kyoung; Choi, Byung-Tae
Abstract : When we evaluated changes of glial fibrillary acidic protein (GFAP) and two glutamate transporter (GTs) by immunohistochemistry, expression of GFAP showed a significant increase in complete Freund's adjuvant (CFA)-injected rats; however, this expression was strongly inhibited by electroacupuncture (EA) stimulation. Robust downregulation of glutamate-aspartate transporter (GLAST) and glutamate transporter-1 (GLT-1) was observed in CFA-injected rats; however, EA stimulation resulted in recovery of this expression. Double-labeling staining showed co-localization of a large proportion of GLAST or GLT-1 with GFAP. Using Western blot, we confirmed protein expression of two GTs, but no differences in the mRNA content of these GTs were observed. Because EA treatment resulted in strong inhibition of CFA-induced proteasome activities, we examined the question of whether thermal sensitivities and GTs expression could be regulated by proteasome inhibitor MG132. CFA-injected rats co-treated with EA and MG132 showed a significantly longer thermal sensitivity, compared with CFA-injected rats with or without MG132. Both EA and MG132 blocked CFA-induced GLAST and GLT-1 downregulation within the spinal cord. These results provide evidence for involvement of GLAST and GLT-1 in response to activation of spinal astrocytes in an EA antinociceptive effect. Antinociceptive effect of EA may be induced via proteasome-mediated regulation of spinal GTs.